PENGEMBANGAN BUKU AJAR LITERASI MATEMATIKA UNTUK PEMBELAJARAN DI SMP - Fatimatul Khikmiyah; Midjan Midjan (Jurnal Silogisme : Kajian Ilmu Matematika dan Pembelajarannya, 2017)
A Capability that includes the five competencies in accordance with the purpose of learning mathematics (NCTM 2000 and Depdiknas 2006) is the mathematical literacy. Although Indonesia has been participated in PISA since 2000, the students’ mean score did not sufficient yet particularly in mathematics. Students get difficulties in solving unfamiliar problems although the mathematics content is the same. Mathematical literacy is not spread yet so that teaching materials that are used to improve the literacy skills are limited. During learning process, students used the literature that loads the basic concepts of mathematics but used  few contexts. Therefore, the researchers conducted a research which the aims to develop a teaching material that can be used to develop students’ mathematical literacy. The method used is ADDIE model which is an acronym for Analysis, Design, Development, Implementation, and Evaluation. Subjects in research is the ninth grade students of SMP N 3 Gresik which are given opportunities to assess the textbooks. From this study, we develop a mathematical literacy module for junior high school students. From the math experts we got the average percentage is 90,18% and 88,64% from the desgn experts.Meanwhile students 81,41 %. Key Words: PISA, Module, Mathematical Literacy, ADDIE model